Some girls [videorecording (DVD)] : live in Texas '78 (Eagle Vision, 2011)
"The Rolling Stones 1978 tour of the USA in support of that year's 'Some Girls' album is considered by fans to be one of their very best.... This concert is typical of the tour with The Rolling Stones delivering a raw, energetic performance in front of a crowd who are clearly loving the show"--Container.